Propiverine increases urethral wall catecholamine levels and bladder leak point pressure in rats. (27th October 2015) - Nishijima, Saori; Sugaya, Kimio; Kadekawa, Katsumi; Ashitomi, Katsuhiro; Ueda, Tomoyuki; Yamamoto, Hideyuki
Abstract : Objective: To investigate whether propiverine has a noradrenaline re‐uptake inhibitor and whether it acts on the lumbosacral cord or the urethral wall. In addition, we aimed to examine the effect of propiverine on leak point pressure in rats. Methods: A total of 72 female and 30 male rats were used to examine the following: (i) the change of leak point pressure caused by intravenous agents in rats with vaginal distention; (ii) the change of leak point pressure caused by intrathecal agents in rats with vaginal distention; (iii) the noradrenaline re‐uptake inhibitor action of propiverine; and (iv) catecholamine levels in the bladder wall, urethral wall, cerebrospinal fluid and plasma after oral administration of propiverine. Results: Intravenous injection of propiverine, imipramine and duloxetine increased the leak point pressure in rats with vaginal distention. Intrathecal naftopidil decreased the leak point pressure, whereas subsequent intravenous propiverine restored the leak point pressure to the level before intrathecal naftopidil in rats with vaginal distention. Propiverine acted like a noradrenaline re‐uptake inhibitor, increasing noradrenaline and/or dopamine levels in the plasma, cerebrospinal fluid, and urethral wall perfusion fluid. Conclusion: Propiverine inhibits noradrenaline re‐uptake, as well as having antimuscarinic and Ca‐antagonist actions. The inhibition of noradrenaline re‐uptake by propiverine mainly occurs at the urethral level and partially in the central nervous system, and might stimulate the smooth muscle of the bladder neck and proximal urethra through α1‐adrenergic receptors, as well as stimulating the striated muscle of the urethra and pelvic floor by activation of spinal motoneurons. Therefore, propiverine might be effective for both stress and urge incontinence.